An Analysis of the Circumstances of Tolerance Status Among University Students - Maqbool, Fahad; Ahmed, Shehzad; Akram, Khadija (Pakistan Journal of Humanities and Social Sciences, 2021)
The study was conducted to analyse the need for a training manual for undergraduate students to promote tolerance through heritage education. The objective of the study was to probe the observations of faculty members regarding the status of tolerance among university undergraduate students. This study was qualitative. The population of the study consisted of public sector universities of province Punjab. A total of 20 faculty members were selected through a simple random sampling technique. The researcher used the semi-structured interview schedule to investigate the perception of faculty members. Nvivo software was used for qualitative data analysis. The qualitative investigation indicated that the students' behavior is often intolerant. Results showed that two significant factors that contribute to intolerance among students were caste and gender differences respectively. Religion also plays an essential role in the occurrence of such incidents, which develop a situation of doing or dying. The intolerance towards different faiths and sects was observed. Students often did not show harmony and respect for others. Lack of balance and non-acceptability of others’ opinions creates conflict.